Peran Produk Pembiayaan Terhadap Kesejahteraan Masyarakat Pada BMT "Akbar" Polokarto, Sukoharjo - Arumastuti, Agnetia, Lukman Hakim, S.E., M.Si (2016)
This study aims to determine the role of financing products for the welfare of society and to know what are the constraints faced and how the efforts to overcome the obstacles on the BMT "Akbar" branch polokarto. This research uses qualitative model with data collecting technique uses interview, observation and documentation. Qualitative data analysis techniques using triangulation sources, methods, timing and theory. Data obtained largely sourced from interviews with the BMT, customers and some of the data from BMT "Akbar" documentation. The results of the study are: 1) BMT contribute positively to the welfare of society in various sectors, namely: a) Trade sector, financing used for additional working capital, and used for the purchase of trade customers needs. b) Industrial sector, used to purchase raw materials for herbal medicine, soy in tofu industry, for industrial wood waste is used to make handycrafts and stalls, buy equipment and to buy machinery. c) Agriculture sector, used to buy seeds, agricultural tools, fertilizers, water, insecticides and to pay for labor. d) Services sector, used to buy sewing machines in sewing services, buying a washing machines in the laundry sevices and the purchase of iron and argon welding wire in the workshop services. e) Fisheries sector, used to buy fish feed maker and buyraw materials for fish feed. 2) constraints faced by bmt, namely: a) constraints in the areas of marketing, when the initial stand BMT image in the eyes of the public is less good and their competitive claims. b) Constraints in the operational field, their financing jammed and their lack of understanding of customers on Islamic economic. While efforts will be undertaken to overcome these obsstacles is to approach the public and instil the notion of Islamic economics, approach the bad debt in order to repay loans and improve system and performance BMT.